Sex or surgery : erectile dysfunction after radical treatment of localized prostate cancer - Lesko Kelović, Vesna (Array, 2009)
Abstract: The maintenance of satisfactory quality of life is major concern in majority of patients who elect treatment for localized prostate cancer. We conducted a cross-sectional study to determine sexual function after radical prostatectomy (RP) and external beam radiotherapy (EBRT). Study population consisted of series of 57 patients with early-stage adenocarcinoma of the prostate, treated in our institution in the period from January 2003 till December 2003. Thirty three patients underwent radical retropubical prostatectomy and 24 patients were treated by primary radical radiotherapy. Patients have been given the full international index of erectile function (IIEF) questionnaire two to four and six months after the treatment. Post treatment sexual function in patients treated by EBRT is significantly better than in patients treated by RP (48,5% vs. 21.57%, p<0,0001). Subgroup analysis reveals that satisfaction with erectile function, maintaining of sexual intercourse and possibility of ejaculation is better in patients treated by EBRT than in patients treated by RP (44.67% vs. 11.57%, p <0,0001) as well as general satisfaction with quality of sexual life (48.5% in EBRT group vs. 21.57% in RP group, p <0,0001). On the other hand, sexual desire remains the same in both groups of patients (63.75% in EBRT group vs. 60.61% in RP group, p = 0.71). Six months after surgical or radiotherapy treatment erectile function is almost as twice as worse in patients treated by surgery than in patients treated by radiotherapy